Systematic review and meta-analysis of the impact of abnormal expression of long non coding RNA on the prognosis of acute myeloid leukemia - Liu, Guihong; Sun, Liangliang; Lv, Peng; Qiao, Rong; Wang, Lihang; Jin, Arong (Frontiers in Genetics, 2025)
ObjectiveLong non-coding RNA (lncRNA) is aberrantly expressed in a variety of tumor diseases. To date, its specific role in acute myeloid leukemia (AML) has not been fully elucidated. This study aims to evaluate the association between aberrant lncRNA expression and poor prognosis in AML patients, and to systematically assess the relationship between aberrant lncRNA expression and AML prognosis.MethodsWe conducted a comprehensive literature search in PubMed, Embase, Cochrane Library, CNKI (China National Knowledge Infrastructure), WanFang (China Wanfang Database), VIP (China VIP Database), and Sinomed (China Biomedical Literature Database) to identify relevant Chinese and English articles. The search period covered from the inception of these databases to 4 August 2024. Articles were screened according to predefined inclusion and exclusion criteria, and meta-analysis was performed using Stata.ResultsA total of 25 articles were included in the analysis. Aberrant lncRNA expression was significantly associated with reduced overall survival (univariate HR = 2.46, 95%CI 2.11–2.88, P < 0.001; multivariate HR = 2.46, 95%CI 2.11–2.88, P < 0.001), event-free survival (HR = 1.51, 95%CI 1.19–1.90, P = 0.001), recurrence-free survival (HR = 2.82, 95%CI 2.03–3.91, P < 0.001), and disease-free survival (HR = 2.390, 95%CI 1.037–5.507, P = 0.041). These findings were statistically significant. The 25 articles collectively identified 22 lncRNAs whose aberrant expression was associated with AML prognosis. Notably, multiple studies highlighted the aberrant expression of lncRNA CRNDE, ZEB2-AS1, and TUG1 as being particularly relevant to AML prognosis. Our meta-analysis revealed that high expression of lncRNA CRNDE and TUG1 was associated with reduced overall survival, while high expression of lncRNA ZEB2-AS1 was linked to decreased disease-free survival, both with statistically significant differences.ConclusionThe expression levels of lncRNAs are closely associated with the prognosis of AML patients and may serve as important indicators for monitoring prognosis in the future. However, further high-quality studies are needed to validate these findings.